2018
DOI: 10.1021/acs.jproteome.7b00503
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signature of Endometrial Cancer

Abstract: Endometrial cancer (EC) is the most common cancer of the female reproductive tract in developed countries. At the moment, no effective screening system is available. Here, we evaluate the diagnostic performance of a serum metabolomic signature. Two enrollments were carried out, one consisting of 168 subjects: 88 with EC and 80 healthy women, was used for building the classification models. The second (used to establish the performance of the classification algorithm) was consisted of 120 subjects: 30 with EC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 37 publications
3
91
0
1
Order By: Relevance
“…Importantly, we observed a strong lipid‐dominant metabolomic profile of lethal metastatic disease, including elevated ketone bodies (BHBA), and acyl glycine/acyl carnitine, dicarboxylic and monohydroxy fatty acids, and lower serum lysophospholipid 1‐linoleoyl‐GPC (18:2). Alterations of BHBA potentially drive tumor progression and metastasis, and higher circulating BHBA has been associated with other cancers including liver, esophagus, ovary and endometrium . The higher circulating fatty acids we identified in cases with metastatic disease could indicate de novo biosynthesis or lipolytic triglyceride mobilization of fatty acids in response to the increased membrane lipid bilayer and cell proliferation requirements of these aggressive cancers .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, we observed a strong lipid‐dominant metabolomic profile of lethal metastatic disease, including elevated ketone bodies (BHBA), and acyl glycine/acyl carnitine, dicarboxylic and monohydroxy fatty acids, and lower serum lysophospholipid 1‐linoleoyl‐GPC (18:2). Alterations of BHBA potentially drive tumor progression and metastasis, and higher circulating BHBA has been associated with other cancers including liver, esophagus, ovary and endometrium . The higher circulating fatty acids we identified in cases with metastatic disease could indicate de novo biosynthesis or lipolytic triglyceride mobilization of fatty acids in response to the increased membrane lipid bilayer and cell proliferation requirements of these aggressive cancers .…”
Section: Discussionmentioning
confidence: 81%
“…Alterations of BHBA potentially drive tumor progression and metastasis, 36 and higher circulating BHBA has been associated with other cancers including liver, esophagus, ovary and endometrium. [37][38][39][40] The higher circulating fatty acids we identified in cases with metastatic disease could indicate de novo biosynthesis or lipolytic triglyceride mobilization of fatty acids in response to the increased membrane lipid bilayer and cell proliferation requirements of these aggressive cancers. [41][42][43] Upregulated fatty acid biosynthesis is also critical for increased acylcarnitine beta-oxidation for mitochondrial ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways have been suggested to be dysregulated in EC, including the lipid metabolism, by comparing cancer tissue samples with tissue from healthy controls [26]. Moreover, a distinct metabolomic signature of EC has been suggested by an Italian pilot study using different models [27]. A population-based case-control study also identified potential biomarkers in relation to EC which were independent of risk factors like obesity and previously known blood samples, and the authors suggest that metabolic profiling may be important in its early detection and risk assessment [28].…”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic biomarker signature has also been proposed based on urine metabolomics profiling in EC [33]. A study among subjects with and without EC showed that the metabolic signature differed from both healthy controls, as well as from benign endometrial disease and other gynecological cancers [27].…”
Section: Discussionmentioning
confidence: 99%
“…A alanina e a tirosina foram identificadas como marcadores de idade em remadores, analisados em a 2 semanas consecutivas de treinamento 10 e o ácido lático, a progesterona, a homocisteína, o 3hidroxibutirato, o ácido linoleico, o ácido esteárico e a valina se mostraram potenciais biomarcadores para câncer do endométrio. 43 Maruyama et al Sugere que seja estudado a relação entre os fragmentos das titina, que são filamentos que mantém as estruturas dos sarcômeros, com as distrofias musculares, principalmente as causadas por doenças musculares quanto as provocadas por exercício físico e, também, o processo de recuperação. 44…”
Section: Metabolômicaunclassified